Sudden Respiratory Failure due to Tracheobronchomalacia by Relapsing Polychondritis, Successfully Rescued by Multiple Metallic Stenting and Tracheostomy - Oryoji, Daisuke (Intern Med, 2017)
Relapsing polychondritis (RP) is a rare systemic autoimmune disease that affects cartilaginous structures. RP causes tracheobronchomalacia (TBM) by affecting the bronchial cartilage. TBM is a fatal condition characterized by excessive weakening of the walls of the trachea and bronchi. We herein report a case of a 73-year-old man who experienced sudden respiratory failure due to TBM caused by RP. Immunosuppressive treatment did not improve his respiratory failure. Multiple metallic stentings dramatically improved his severe airway symptoms. When the airway condition becomes lethal in RP patients, then metallic stenting can be a useful treatment option.